Utilization and Primary Survey of Timber Yielding Plants in Tribal Region of PethTaluka, Nashik, India - Avinash.S.Jondhale; Smita .P.Chavan (International Journal of Pharma and Bio Sciences, 2021)
PethTaulka region is selected for our experimental study. About 99.00% of the population belongs to tribal community. The life and livelihood of the tribes depends on forest resources plants as they provide all the commodities required by them in their everyday life. However, nowadays there is a rapid depletion of these valuable forest resources timber yielding trees. Therefore, in the present investigation, a primary survey of timber yielding plants and their utilization was carried out in the PethTaluka. In the present study an attempt has been to ascertain the current status of timber yielding plant species in forest region of experimental area. The study was carried out during 2017 - 2018 and 2018-19 through interactions with different tribal communities in the Perth region. Then, the utilization of timber yielding plants data were confirmed on the basis of personal interview with local inhabitants and also personal observations. As per experimental result, we observed that, 30 timber plants species were used by tribal people for various purposes like, agricultural implements, house construction, furniture and musical instruments. Therefore, overall experimental reports on 30 timber yielding plant species belonging to 25 genera and 17 families are used as wood resources in the forest area of PethTaluka. Among plant families Fabaceae is a dominant family with 08 species followed by Combretaceae having 04 species and Meliaceae, Myrtaceae and Moraceae each having 02 species. Therefore, conservation and propagation of timber yielding plants is necessary for forest protection and environmental balance.